Behavioral intervention for sleep problems in childhood: a Brazilian randomized controlled trial - El Rafihi-Ferreira, Renatha; Nogueira Pires, Maria Laura [UNESP]; Mattos Silvares, Edwiges Ferreira de (Springer, 2019)
Background: Sleep problems are common in children and can have an effect on behavioral and emotional functioning. Despite the importance of sleep for children's health, there is a lack of studies on this topic in Brazil. The aim of this study was to evaluate the efficacy of behavioral intervention for sleep problems in young children and to investigate the effects on their daytime behavior. Methods: Sixty-two children (ages 1-5; M = 2.3, SD = 1.3) with bedtime problems and night waking were randomized to a parent-based intervention or a wait list control group. After the waiting period, the wait list participants were offered treatment. The intervention was composed of five sessions over 2 months, during which the parents were educated on their child's sleep and received guidance on the establishment of sleeping schedules and routines and on the use of extinction and positive reinforcement techniques. Sleep patterns and behavior problems were assessed with parent-report measures. Sleep patterns were also assessed with actigraphy. Assessments were completed at pre-intervention, post-intervention, 1-month follow-up, and 6-month follow-up. Results: Children who received intervention showed greater baseline to post-treatment improvements in sleep latency, night waking, behavior such as resisting going to bed, the desire to sleep with their parents, and daytime behavior than the control group. These improvements were maintained at follow-up. Conclusions: We concluded that behavioral parent-based intervention is effective in improving the quality of sleep and the diurnal behavior of children. This study provides initial support for use of this protocol in psychology clinics/schools. Brazilian clinical trials registration, RBR-4kxxd5. Retrospectively registered on December 13, 2016.
Keywords: Behavioral intervention; Sleep problems; Behavior; Children; Sleep